Associations of changes in reported and estimated protein and energy intake with changes in insulin resistance, glycated hemoglobin, and BMI during the PREVIEW lifestyle intervention study. Issue 5 (10th August 2021) - Drummen, Mathijs; Adam, Tanja C; Macdonald, Ian A; Jalo, Elli; Larssen, Thomas M; Martinez, J Alfredo; Handjiev-Darlenska, Teodora; Brand-Miller, Jennie; Poppitt, Sally D; Stratton, Gareth; Pietiläinen, Kirsi H; Taylor, Moira A; et al.
ABSTRACT: Background: Observed associations of high-protein diets with changes in insulin resistance are inconclusive. Objectives: We aimed to assess associations of changes in both reported and estimated protein (PRep ; PEst ) and energy intake (EIRep ; EIEst ) with changes in HOMA-IR, glycated hemoglobin (HbA1c), and BMI (in kg/m 2 ), in 1822 decreasing to 833 adults (week 156) with overweight and prediabetes, during the 3-y PREVIEW (PREVention of diabetes through lifestyle intervention and population studies In Europe and around the World) study on weight-loss maintenance. Eating behavior and measurement errors (MEs) of dietary intake were assessed. Thus, observational post hoc analyses were applied. Methods: Associations of changes in EIEst, EIRep, PEst, and PRep with changes in HOMA-IR, HbA1c, and BMI were determined by linear mixed-model analysis in 2 arms [high-protein-low-glycemic-index (GI) diet and moderate-protein-moderate-GI diet] of the PREVIEW study. EIEst was derived from energy requirement: total energy expenditure = basal metabolic rate × physical activity level; PEst from urinary nitrogen, and urea. MEs were calculated as [(EIEst − EIRep )/EIEst ] × 100% and [(PRep − PEst )/PEst ] × 100%. Eating behavior was determined using the Three Factor Eating Questionnaire, examining cognitive dietary restraint, disinhibition, and hunger. Results: Increases in PEst and PRep and decreases in EIEst and EIRep were associated with decreases in BMI, but not independently with decreases in HOMA-IR. Increases in PEst and PRep were associated with decreases in HbA1c. PRep and EIRep showed larger changes and stronger associations than PEst and EIEst . Mean ± SD MEs of EIRep and PRep were 38% ± 9% and 14% ± 4%, respectively; ME changes in EIRep and En% PRep were positively associated with changes in BMI and cognitive dietary restraint and inversely with disinhibition and hunger. Conclusions: During weight-loss maintenance in adults with prediabetes, increase in protein intake and decrease in energy intake were not associated with decrease in HOMA-IR beyond associations with decrease in BMI. Increases in PEst and PRep were associated with decrease in HbA1c. This trial was registered at clinicaltrials.gov as NCT01777893.